2019
DOI: 10.1016/j.celrep.2019.04.047
|View full text |Cite
|
Sign up to set email alerts
|

The Hippo Pathway Blocks Mammalian Retinal Müller Glial Cell Reprogramming

Abstract: SUMMARY In response to retinal damage, the Müller glial cells (MGs) of the zebrafish retina have the ability to undergo a cellular reprogramming event in which they enter the cell cycle and divide asymmetrically, thereby producing multipotent retinal progenitors capable of regenerating lost retinal neurons. However, mammalian MGs do not exhibit such a proliferative and regenerative ability. Here, we identify Hippo pathway-mediated repression of the transcription cofactor YAP as a core regulatory mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
101
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(127 citation statements)
references
References 91 publications
4
101
2
1
Order By: Relevance
“…4J). In mice, we observed that a subset of gliotic MG resembled the proliferative branch in the zebrafish trajectory, which is consistent with observations that mouse MG transiently upregulate cell cycle regulators such as Ccnd1 and Cdk4 following injury (5,19). In zebrafish, MG in the resting, gliosis and proliferative branches were close to chick MG from corresponding branches ( Fig.…”
Section: Comprehensive Profiling Of Mg From Zebrafish Chick and Moussupporting
confidence: 89%
See 2 more Smart Citations
“…4J). In mice, we observed that a subset of gliotic MG resembled the proliferative branch in the zebrafish trajectory, which is consistent with observations that mouse MG transiently upregulate cell cycle regulators such as Ccnd1 and Cdk4 following injury (5,19). In zebrafish, MG in the resting, gliosis and proliferative branches were close to chick MG from corresponding branches ( Fig.…”
Section: Comprehensive Profiling Of Mg From Zebrafish Chick and Moussupporting
confidence: 89%
“…S21A). YAP was recently shown to be required for MG to exit quiescence in both Xenopus and mice (5,19). We found that morpholino-mediated knockdown of Yap1 protein in the light-damaged zebrafish retina significantly reduced the number of proliferating MG relative to the Standard Control morphant ( Fig.…”
Section: Functional Validation Of Candidate Genes That Regulate Prolimentioning
confidence: 54%
See 1 more Smart Citation
“…Because the regenerative effects of activating Yap in organs such as the retina and heart have been characterized extensively 5,14,15,17 , we investigated whether TRULI treatment is effective in eliciting cellular proliferation in these contexts.…”
Section: Effects Of Truli On Cardiomyocytes and Müller Gliamentioning
confidence: 99%
“…The regenerative potential of the Hippo pathway has become abundantly clear in numerous organs, including the heart 5, [14][15][16] , retina 17 , liver, and intestine 18 . We earlier demonstrated that Hippo signaling limits the size of the developing murine utricle, a vestibular sensory organ, and that the Yap-Tead complex is active during-and necessary for-proliferative regeneration in the neonatal utricle 19 .…”
Section: Introductionmentioning
confidence: 99%